Efficient utilization of licorice root by alkaline extraction - Ohno, Hirokazu; Miyoshi, Shozo; Araho, Daisuke; Kanamoto, Taisei; Terakubo, Shigemi; Nakashima, Hideki; Tsuda, Tadashi; Sunaga, Katsuyoshi; Amano, Shigeru; Ohkoshi, Emika; Sakagami, Hiroshi; Satoh, Kazue; et al. (In vivo (Athens), 2014)
Compared to studies of water extracts of plants, those utilising alkaline extracts are limited. Both water and alkaline extracts from licorice root were compared regarding their biological activities. Licorice root was successively extracted first with water or alkaline solution (pH 9 or 12), and the alkaline (pH 12.0) extract was further separated into 50% ethanol-soluble and -insoluble fractions. Viable cell number was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method. Antibacterial activity against Porphyromonas gingivalis 381 was determined by turbidity assay. Cytochrome P-450 (CYP)3A4 activity was measured by β-hydroxylation of testosterone using human recombinant CYP3A4. Radical intensity of superoxide and hydroxyl radicals was determined by electron spin resonance spectroscopy. Alkaline extraction yielded slightly higher amounts of dried materials compared to water extraction. Alkaline extract showed higher anti-HIV and antibacterial activities, and similar magnitudes of CYP3A4 inhibitory and superoxide and hydroxyl radical-scavenging activities, compared to water extract. When alkaline extract was fractionated by 50% ethanol, anti-HIV activity was recovered from the insoluble fraction representing approximately 3% of the alkaline extract, whereas antibacterial activity was concentrated in the soluble fraction rich in glycyrrhizid acid, flavanones and chalcones. All extracts and sub-fractions led to bimodal hormetic dose-response (maximum hormetic response=238%) on the bacterial growth. The present study demonstrated the superiority of alkaline extraction over water extraction for preparing anti-HIV and antibacterial agents at higher yield from licorice root.